Practical Tips for Home and Yard, Yard Care and the Environment - Mayer, Steve; Neier, Bob; Warminski, Norman C.; Graber, Debra; Upham, Ward (My University, 1998)
This publication provides specific information about pesticides, fertilizers, landscaping, watering, and related topics.
MF2132_1998_11
Keywords: MF2132; Lawn and Garden; Environment and Natural Resources; MF